Penerapan E-Test Pada Mata Pelajaran Bahasa Inggris Menggunakan Model View Controller - Sri Restu Ningsih; Erdisna Erdisna; Febriyanno Suryana; Yenni Desnelita; Silfia Andini (Ikatan Ahli Informatika Indonesia (IAII), 2023)
The problem that occurs in one of the high schools is that there is no online-based English exam system, and they still use paper for their assessments. This makes teachers unable to give exams to students if they do not attend school. The purpose of this research is to create an online exam system to facilitate exam administration using the Model View Controller (MVC) to assess online English exams. The analytical method uses the System Usability Scale (SUS), to collect data using an electronic test (e-Test).Unifield Modeling Language (UML), a visual modeling technique used in designing and building object-oriented software for E-Test applications.The results showed that the use of the E-test application in a comparison class in English subjects could improve student learning outcomes to a higher level, from a score of 81.7 to 90.9. Compared to the control class, there was a slight increase, namely an increase in value from 71.5 to 75.8. This proves that the E-test application is used effectively by students for English subjects.